Inborn metabolic diseases: diagnosis and treatment - Fernandes, John; Saudubray, Jean-Marie; Berghe, Georges; Tada, K.; Buist, N. R. M. (Springer Berlin Heidelberg Imprint: Springer, 1995)
The diagnosis of metabolic diseases is facilitated by this clinical book. Each disease-related chapter begins with a detailed description of the patient and the delineating symptoms necessary for establishing the diagnosis and differential diagnosis. The figures illustrate the metabolic derangement in a uniform way, thus affording clarification and better understanding of the treatment. The metabolic derangement is discribed in great detail, together with essential aspects of the genetics involved. The topics covered range from general aspects such as the clinical approach to metabolic diseases, emergency treatment, diagnostic procedures, and psychosocial care for the child and the family to specific dicussions of new modes of treatment, including liver transplantation, bone marrow transplantation, and somatic gene therapy